MENELISIK MITOS DEWI LANJAR DAN MITOS RATU KIDUL DENGAN PERSPEKTIF ANTROPOLOGI-STRUKTURAL - Barata, Nugroho Trisnu (Forum Ilmu Sosial, 2013)
This article aims to analyzing of myth phenomenon on the parth of Javanese life in Northern Java Island (Lanjar Goddes myth) and Southern Java Island (South Queen myth). Questions to elaborate in this paper include; (1) How the narration of description about Lanjar Goddes myth and South Queen myth on Javanes life?; and (2) How the structure behind Lanjar Goddes myth and South Queen myth? The method used in this study is litherature study, that is the text of Lanjar Goddes myth and the text of South Queen myth. In this article the paradigm used is structuralism theory. The relations between actor and event can be transformed or to changed on position relations form that can seen relations network between actor and event, domain, and character on one model. There are four main actors on these myth are Lanjar Goddess (Dewi Lanjar), South Queen (Ratu Kidul), King Senopati (Panembahan Senopati), and Lord Bahu (Raden Bahu). The naration context is Java Island or Javanese culture. Episode of actor context and event, conflict episode, and conflict resolution episode seen the same relations and opposite relations. Man-women relation, sea-continent relation, alliance-defeate relation can seen on both two myths narration.Â